The Impact of Islamic Religious Education on the Development of Social Character Among Secondary School Students - Rahman, Syarif; Agustami, Eli; Effendi, Syamsul; Padang, Ramlan; Guchi, Zulkarnaen (PT Inovasi Pratama Internasional, 2024)
The objective of this study is to investigate and analyze the impact of Islamic education on the social-emotional development of students at ABC MTs. This research employs a qualitative approach utilizing case study methodology to gain insight into the subject matter. Data collection techniques include participatory observation, in-depth interviews with teachers and learners, and document analysis pertaining to curriculum and Islamic educational activities at ABC MTs. The findings of this study indicate that Islamic education at ABC MTs plays a significant role in fostering social and emotional growth in students. The Islamic education programme at ABC MTs instills Islamic moral and ethical values through religious learning and worship practices. These facilitate learners' awareness of social responsibility, concern for others, and the ability to manage and cope with emotions when interacting with others. The comprehensive Islamic education curriculum, integrated with general education, provides a strong foundation for the development of learners' social-emotional skills. Furthermore, ABC MTs also emphasises character education through the provision of examples and guidance by teachers and staff who serve as Islamic role models. In addition to this, the supportive environment of a pesantren, along with the social norms applied, play an important role in the shaping of social-emotional qualities. The outcomes of this study offer insights and a better understanding of the contribution of Islamic education in the social-emotional development of learners at ABC MTs. These findings can be used as a reference point for other Islamic education institutions in strengthening the social-emotional dimensions of learners through an integrated approach between religious education, character, and the educational environment.